Experimental and model analyses of laminar combustion characteristics of variable composition CO/H2/CH4 mixtures at high N2 and CO2 concentrations. (7th May 2020) - Zhang, Qiaosheng; Chen, Guoyan; Wang, Fahui; Deng, Haoxin; Wen, Xiaoping; Zhang, Anchao; Sheng, Wei
Summary: The effect of variable composition CO/H2 /CH4 mixtures (15%‐20% CO, 5%‐20% H2, 0%‐15% CH4 ) at high diluent ratios (15% CO2 and 50% N2 ) on laminar combustion characteristics has been studied by experiment and numerical simulation. The laminar burning velocities (LBVs) of seven biomass‐derived gases in an equivalent ratio of 0.6 to 1.4 have been experimentally measured by the spherical expansion flame method under ambient conditions. The experimental results obtained based on the linear and nonlinear extrapolation methods were compared with the data in the literature and the predictions of four detailed chemical kinetic models (FFCM‐1, GRI 3.0, USC II, San Diego 2016). The results show that an increase in the equivalence ratio or a decrease in the H2 fraction in the mixture is beneficial to the reduction of the LBV difference obtained by the linear and nonlinear extrapolation methods. With the increase of H2 fraction in the mixture, the highly thermally diffusive fuel significantly enhanced the LBV and the maximum LBV leaned toward the fuel‐rich side. For mixtures with a higher CH4 fraction than H2, it has the lowest LBV but has the higher adiabatic temperature and heat release. The predictions of the four models show that for all different composition mixtures, San Diego 2016 has over‐predicted on the lean side. The FFCM‐1 and GRI 3.0 matched better with the experimentally measured LBV of the H2 ‐rich mixture. With the increase of CH4 fraction relative to H2, the prediction of USC II is slightly reduced on the rich side, and all the predictions under stoichiometric conditions are overpredicted compared to the experimental data. Sensitivity analyses are performed on flames of the mixture with different compositions at Φ = 0.8 and 1.2, it is found that with the addition of CH4 fraction to the mixture, R1 gradually became the most dominating reaction, which has a stronger effect on LBV. Furthermore, the reaction paths and heat release of different composition mixtures under stoichiometric conditions are analyzed. The Markstein lengths of variable composition mixtures at different equivalence ratios are studied. It suggested that the Markstein length gradually decreases with the increase of CH4 in the fuel, thus the stretched flame speed is more susceptible to flame stretch rate and the flame stability decreases. Abstract : Combustion characteristics of biomass syngas